Drug Induced Hypersensitivity and the HLA Complex - Munir Pirmohamed; Ana Alfirevic (MDPI AG, 2010)
Drug-induced hypersensitivity reactions are of major concern and present a burden for national healthcare systems due to their often severe nature, high rate of hospital admissions and high mortality. They manifest with a wide range of symptoms and signs, and can be initiated by a wide range of structurally diverse chemical compounds. The pathophysiological mechanisms underlying hypersensitivity reactions are not well understood, but it is thought that they are immune mediated. MHC region on Chromosome 6 contains many genes with immune function. Classical MHC molecules are highly polymorphic cell surface glycoproteins whose function is to present peptide antigens to T cells. In addition to conferring protection from some diseases, HLA alleles are also associated with an increased risk of other diseases, including drug-induced hypersensitivity. Pharmacogenetic approach to predict the risk of drug-induced hypersensitivity has been established for several drugs. We will discuss the progress of hypersensitivity pharmacogenetics over the last few years and focus on current efforts of the international community to develop consortia which aim to standardize disease phenotypes and to identify affected individuals through international collaborations. In addition, we will discuss the clinical utility of HLA typing as predictive or diagnostic testing for drug-induced hypersensitivity.